Class and power in Roman Palestine the socioeconomic setting of Judaism and Christian origins - Keddie, Anthony ca. 20./21. Jh. (New York Cambridge University Press, 2019)
Examines how socioeconomic relations between Judaean elites and non-elites changed as Palestine became part of the Roman Empire.
Cover -- Half-title -- Title page -- Copyright information -- Dedication -- Table of Contents -- List of Figures -- List of Tables -- Acknowledgments -- Note on the Text -- Abbreviations -- Introduction -- Chapter 1 Urban Development and the New Elites -- Urban Development and Elite Power -- The Persistence of Toparchies -- The Decapolis and Coastal Cities in Transition -- Urban Development in Jerusalem -- Urban Development in the Galilee -- Rural Mansions and the Question of "Roman Villas" -- Conclusion -- Chapter 2 Land Tenancy and Agricultural Labor -- The Theory of Roman Proletarianization -- Land Tenancy from the Iron Age to the Hasmoneans -- Early Roman Tenancy and the Expansion of Private Land -- Estate Fragmentation and Landowner-Tenant Relations -- Balancing the Debt Spiral -- Conclusion -- Chapter 3 Taxation -- Elites and the Introduction of Roman Tributes -- Censuses and the Regulation of Tributes -- Indirect Taxes -- Elites, Indirect Taxes, and Market Oversight -- Conclusion -- Chapter 4 Economy of the Sacred -- Religion and Economics in the Roman East -- Jerusalem's Temple Economy -- Tithes -- Conflicting Institutions in the Torah -- Changes under the Hasmoneans -- Tithing in the Early Roman Period -- The Temple Tax -- Conclusion -- Chapter 5 Material Culture from Table to Grave -- The Archaeology of Class -- Tableware -- Oil Lamps -- Dress -- Mortuary Practices -- Non-elite Burial -- Elite Burial -- The Material Culture of Burial -- Burial and Class Distinction in Texts -- Conclusion -- Conclusion -- Institutional Change and Political Power -- Institutional Change and Economic Power -- Institutional Change and Ideological Power -- Appendix A: Herodian Rulers -- Appendix B: High Priests during the Early Roman Period -- Appendix C: Palamyra Duties (137 ce) -- Bibliography -- Index of Ancient Sources -- Index of Subjects.
Description based on publisher supplied metadata and other sources
Keywords: Power (Social sciences)-History-To 1500; Electronic books